Leucine-Rich Repeat Kinase 2 (LRRK2) Stimulates IL-1β-Mediated Inflammatory Signaling through Phosphorylation of RCAN1 - Han, Kyung A.; Yoo, Lang; Sung, Jee Y.; Chung, Sun A.; Um, Ji W.; Kim, Hyeyoung; Seol, Wongi; Chung, Kwang C. (Frontiers in Cellular Neuroscience, 2017)
Leucine-rich repeat kinase 2 (LRRK2) is a Ser/Thr kinase having mixed lineage kinase-like and GTPase domains, controlling neurite outgrowth and neuronal cell death. Evidence suggests that LRRK2 is involved in innate immune response signaling, but the underlying mechanism is yet unknown. A novel protein inhibitor of phosphatase 3B, RCAN1, is known to positively regulate inflammatory signaling through modulation of several intracellular targets of interleukins in immune cells. In the present study, we report that LRRK2 phosphorylates RCAN1 (RCAN1-1S) and is markedly up-regulated during interleukin-1β (IL-1β) treatment. During IL-1β treatment, LRRK2-mediated phosphorylation of RCAN1 promoted the formation of protein complexes, including that between Tollip and RCAN1. LRRK2 decreased binding between Tollip and IRAK1, which was accompanied by increased formation of the IRAK1-TRAF6 complex. TAK1 activity was significantly enhanced by LRRK2. Furthermore, LRRK2 enhanced transcriptional activity of NF-κB and cytokine IL-8 production. These findings suggest that LRRK2 might be important in positively modulating IL-1β-mediated signaling through selective phosphorylation of RCAN1.